(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work the clearer contexts in which the suffix -te appears are studied, particularly formular expressions or short texts, in order to determine, more than the semantic value of the suffix, its position in the Iberian nominal morphology. We conclude that this suffix is very close to genitive -en, even in a certain sense its compementary, and in the same way it’s used in the context of the noun phrase, but refering more to the author than to the possessor of an object.